1999
DOI: 10.1073/pnas.96.3.1036
|View full text |Cite
|
Sign up to set email alerts
|

Distinct dendritic cell subsets differentially regulate the class of immune responseinvivo

Abstract: Dendritic cells (DCs) are unique in their ability to stimulate T cells and initiate adaptive immunity. Injection of mice with the cytokine Flt3-ligand (FL) dramatically expands mature lymphoid and myeloid-related DC subsets. In contrast, injection of a polyethylene glycolmodified form of granulocyte͞macrophage colony-stimulating factor (GM-CSF) into mice only expands the myeloidrelated DC subset. These DC subsets differ in the cytokine profiles they induce in T cells in vivo. The lymphoid-related subset induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
687
6
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 920 publications
(749 citation statements)
references
References 37 publications
51
687
6
5
Order By: Relevance
“…The splenic DC preparation also consisted of about 5% plasmacytoid DC, which were CD11c int , I-Ab -/low and mouse plasmacytoid DC antigen 1 (m-PDCA-1) + . Splenic OT-I CD8 T cells that were freshly isolated or pre-activated with PMA and ionomycin for 2 days were cultured with splenic DC pulsed with either relevant peptide OVA 257-264 or control peptide GP [33][34][35][36][37][38][39][40][41] . After 20 h of co-culture, the expression of CD40, CD80 and CD86 on DC was determined by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The splenic DC preparation also consisted of about 5% plasmacytoid DC, which were CD11c int , I-Ab -/low and mouse plasmacytoid DC antigen 1 (m-PDCA-1) + . Splenic OT-I CD8 T cells that were freshly isolated or pre-activated with PMA and ionomycin for 2 days were cultured with splenic DC pulsed with either relevant peptide OVA 257-264 or control peptide GP [33][34][35][36][37][38][39][40][41] . After 20 h of co-culture, the expression of CD40, CD80 and CD86 on DC was determined by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, DCs from wild-type mice release lower amounts of IL-12 and have the capacity to promote IFN-γ and IL-4 production upon adoptive transfer. We next compared the number of CD8α + and CD8α − DCs in wild-type and μMT mice, since only the subset of DCs expressing CD8α has been shown to produce IL-12 18 19. The data in Table show that the proportion of DC subsets is similar in both strains of mice.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have reported that subclasses of DCs directed the development of distinct T helper cells in vivo 18 19. Thus, CD8α + and CD8α − DCs, purified from spleens, have the potential to differentially regulate the Th1/Th2 balance: CD8α − DCs induced the activation of cells secreting high levels of IL-4, IL-5, and IL-10, and low levels of IL-2 and IFN-γ, whereas CD8α + DCs sensitize cells producing IL-2 and IFN-γ, but little IL-4, IL-5, or IL-10.…”
Section: Discussionmentioning
confidence: 96%
“…Tip-DCs develop later during infection from recruited monocytes and by GM-CSF secreted from T cells at the site of inflammation. Others reported that the steady-state occurring splenic DC subsets (CD8a À , CD8a 1 or plasmacytoid DCs) show intrinsic differences to mount preferentially a Th1-or Th2-cell biased response [8,55,56]. Thus, our BM-DC equivalents to Tip-DCs might play a decisive role in dampening or modulating the initially mounted Th-cell response to effectively eliminate the invading pathogen, a process also referred to as ''success-driven'' Th-cell modulation [57].…”
Section: Discussionmentioning
confidence: 99%